Impactos sobre o desenvolvimento regional decorrentes do Assentamento Itamarati, Ponta Porã (MS): 2001 -2010 - Bellé, Maria de Fátima Lessa; Alves, Gilberto Luiz; Souza, Celso Correia de (Albuquerque (online), 2017)
.